1998
DOI: 10.1073/pnas.95.8.4321
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of inserted foreign epitopes by a channelforming protein

Abstract: Certain bacterial protein toxins are able to insert themselves into, and at least partially across, lipid bilayer membranes in the absence of any auxiliary proteins, by using unknown mechanisms to overcome the high energy barrier presented by the hydrophobic bilayer core. We have previously shown that one such toxin, colicin Ia, translocates a large, hydrophilic part of itself completely across a lipid bilayer in conjunction with the formation of an ion-conducting channel. To address the question of whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…the membrane surface. This suggests that the protein unfolds and spreads out on the surface of the membrane, which is in agreement with the previous proposals for colicin A (26 -28) E1 (29,31,(47)(48)(49) and I a (25,(41)(42)(43). The em max values for W-355 and W-367 single Trp proteins indicate that both helices 1 and 2 are membrane-associated under the conditions used in this study but that the corresponding Trp residues are in a more polar environment than those found within the hydrophobic anchor domain of the channel protein (Table I).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…the membrane surface. This suggests that the protein unfolds and spreads out on the surface of the membrane, which is in agreement with the previous proposals for colicin A (26 -28) E1 (29,31,(47)(48)(49) and I a (25,(41)(42)(43). The em max values for W-355 and W-367 single Trp proteins indicate that both helices 1 and 2 are membrane-associated under the conditions used in this study but that the corresponding Trp residues are in a more polar environment than those found within the hydrophobic anchor domain of the channel protein (Table I).…”
Section: Discussionsupporting
confidence: 81%
“…The em max data for the contingent of single Trp mutant and WT proteins strongly suggest that the polarity of the Trp residues (at 11 of the 14 different Trp sites within the peptide) increases when the protein associates with (51); biotinylation (41,42,53); epitope mapping (43); saturation mutagenesis (55); protease accessibility (28,47); depth-dependent fluorescence quenching (29,31); cysteine-scanning mutagenesis (56); FRET (27); CD, Fourier transform infrared radiation, and differential scanning calorimetry (48,49); time-resolved spin labeling (57); and acrylamide quenching and other fluorescence data presented in this work. The initial surface-bound structure adopts at least two states with state 2 being the most populated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a paper appearing in this issue of Proceedings, Jakes et al Jakes et al (1) found that two inserted peptide epitopes are indeed dragged across the lipid bilayer. They chose the site of insertion for these epitopes based on the crystal structure of colicin Ia in solution (10), placing the heterologous sequences in the loop connecting two ␣-helices in the translocated segment.…”
mentioning
confidence: 99%
“…7). The observation that localized mutations in this transported segment, including insertions of up to 12 residues, do not block its movement (8) suggested that this system might be recruited to translocate suitably attached exogenous proteins.…”
mentioning
confidence: 99%